TECHNOLOGY OF GROWING VEGETABLES IN PROTECTED LANDS - Qodirova, Shaxribonu Normurodovna (Educational Research in Universal Sciences, 2023)
This article covers the intensive technology of growing vegetable crops in homesteads and sheltered areas under rapidly changing climatic conditions.